Quality-checked species records from the German citizen science platform ArtenFinder - Thore Engel; Yannick Brenz; Hendrik Geyer; Jörg Holetschek; Aletta Bonn; Cathrina Balthasar; Susanne Bengsch; Romain Clément; Christian Dietzen; Chris Dlouhy; Jens Esser; Frederic Griesbaum; et al. (Biodiversity Data Journal, 2025)
Volunteers and citizen science initiatives play a crucial role for the documentation of species occurrences and distributions. When quality-checked and openly available, such data can provide information for biodiversity research and nature conservation. While some large international platforms reach a high number of opportunistic users around the world, there are also many smaller and regional citizen science initiatives, which often collaborate very closely with local authorities, conservation organisations and local experts and volunteers. Despite their high quality, data from such regional initiatives are often missing from global open data platforms, such as the Global Biodiversity Information Facility (GBIF).Here, we present a quality-checked citizen science dataset published on GBIF with more than 1 million georeferenced species records with a geographic focus on the German federal states of Rhineland-Palatinate (Rheinland-Pfalz) and Berlin. The dataset originates from the collaborative observation platform ArtenFinder, which is run by the two federal states. While each state branch administers its own web platform, they share a common database. Users can upload, edit, manage and share their observations of animals, plants and fungi. Experts validate the species records, based on photographs and other media as well as on plausibility, which allows the data to be used by state authorities and for conservation management and research purposes. The data mobilisation and publication were enabled by the German National Research Data Infrastructure for Biodiversity (NFDI4Biodiversity) and the dataset is now also available through the Living Atlas of Nature Germany platform, a GBIF hosted portal.